ANALYSIS OF REGIONAL FINANCIAL INDEPENDENCE OF BENGKALIS DISTRICT GOVERNMENT IN THE IMPLEMENTATION OF AUTONOMY AREA - Furqon Nur Islamiati; Isyandi; Any Widayatsari (JURNAL EKBIS, 2024)
This research aims to analyze the influence of balancing funds, local original income (PAD), and capital expenditure on regional financial independence in Bengkalis Regency for the 2013-2022 period. A quantitative approach is used with APBD budget realization report data. The sample in the form of a budget realization report for Bengkalis Regency for 2013-2022 was analyzed using multiple linear regression with the OLS method using the Eviews 10 program. The results show that balancing funds have a significant negative effect on regional financial independence, while PAD has a significant positive effect. Capital expenditure has a positive but not significant effect. Simultaneously, balancing funds, PAD, and capital expenditure influence regional financial independence in Bengkalis Regency. This means that the level of regional financial independence can be explained by these three variables.